2012
DOI: 10.1016/j.radonc.2011.12.029
|View full text |Cite
|
Sign up to set email alerts
|

A phase I/II study of gemcitabine-concurrent proton radiotherapy for locally advanced pancreatic cancer without distant metastasis

Abstract: GPT was feasible and showed high efficacy. Although the number of patients and the follow-up periods are insufficient, the clinical results seem very encouraging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
88
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 109 publications
(94 citation statements)
references
References 29 publications
4
88
0
Order By: Relevance
“…4,6,10,19 Particle therapy, such as carbon ion therapy (CIT) and proton therapy (PT), can deliver high-dose radiation to tumours while minimizing the dose delivered to organs at risk because of its precise dose distribution compared with conventional photon therapy. [22][23][24][25][26][27][28][29][30][31][32] Particle beams possess a physical characteristic called the Bragg peak, which emits a relatively low dose near the body surface and releases the maximum energy just before it stops in the depth. Recently, several investigators have reported on the efficacy of CIT for sacral chordomas, describing high LC rates and low toxicities.…”
mentioning
confidence: 99%
“…4,6,10,19 Particle therapy, such as carbon ion therapy (CIT) and proton therapy (PT), can deliver high-dose radiation to tumours while minimizing the dose delivered to organs at risk because of its precise dose distribution compared with conventional photon therapy. [22][23][24][25][26][27][28][29][30][31][32] Particle beams possess a physical characteristic called the Bragg peak, which emits a relatively low dose near the body surface and releases the maximum energy just before it stops in the depth. Recently, several investigators have reported on the efficacy of CIT for sacral chordomas, describing high LC rates and low toxicities.…”
mentioning
confidence: 99%
“…Recently, SBRT can be applicated in only several days with achieving equivalent to or better tumor control rates than standart CRT regimes altough without CT with limited toxicity especially elderly and low ECOG performance patients with pancreatic cancer [57]. NS and H can also improved to treatment outcomes with using low total dose of radiation with standart IMRT or SBRT methods with or without CT by reducing toxicities and increasing cytotoxic effects [58][59][60][61][62].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, radiation techniques have undergone remarkable developments, resulting in higher radiation doses being prescribed with great accuracy. Several authors reported their attempts to put intensity modulated radiation therapy or particle therapy to the treatment of PC [46][47][48]. Terashima et al showed the feasibility and high efficacy of high-dose proton therapy with GEM [48].…”
Section: Discussionmentioning
confidence: 99%